2014
DOI: 10.1111/ijfs.12554
|View full text |Cite
|
Sign up to set email alerts
|

Enrichment of rice noodles with fibre‐rich fractions derived from cassava pulp and pomelo peel

Abstract: Summary Cassava pulp and pomelo peel were evaluated for their potential as sources of dietary fibre in dried rice noodles. Noodles containing cassava pulp (1–20%) and pomelo peel (1–10%) had significantly higher cooking weight (136–166%) than the control sample (125%). Elongation of noodles containing cassava pulp (61–86%) was significantly higher than that of the control (56%) and noodles containing pomelo peel (29–49%). Total dietary fibre (TDF) content of noodles made from rice flour was 3.0%, and increased… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
26
1

Year Published

2015
2015
2023
2023

Publication Types

Select...
4
2

Relationship

1
5

Authors

Journals

citations
Cited by 36 publications
(30 citation statements)
references
References 17 publications
3
26
1
Order By: Relevance
“…Thus, the presence of natural yellow pigment (flavonoid) in WRP might have contributed to the yellow color of WRP-containing noodles. In addition, the results of b* value obtained from the present study showed a similar trend with those reported by Wandee et al (2014), who reported that the pomelo peelincorporated rice noodle possesses a greater yellow value (b*) than control.…”
Section: Color Of Noodlessupporting
confidence: 91%
See 3 more Smart Citations
“…Thus, the presence of natural yellow pigment (flavonoid) in WRP might have contributed to the yellow color of WRP-containing noodles. In addition, the results of b* value obtained from the present study showed a similar trend with those reported by Wandee et al (2014), who reported that the pomelo peelincorporated rice noodle possesses a greater yellow value (b*) than control.…”
Section: Color Of Noodlessupporting
confidence: 91%
“…This indicated that the substitution of WRP for wheat flour did not affect the L* of noodles. Several studies recorded lower L* value, when non-wheat flours, such as green banana flour (Saifullah et al, 2009), sweet potato flour (Zhang, Sun, He & Tian, 2010), pomelo peel flour (Wandee et al, 2014), and kenaf seeds flour (Zawawi et al, 2014), replaced wheat flour. Other authors reported the substitution of composite flour such as taro increased the L* value of noodle (Kaushal & Sharma, 2014).…”
Section: Color Of Noodlesmentioning
confidence: 99%
See 2 more Smart Citations
“…These by-products cause a major disposal problem for the industry. However, they still contain a lot of nutrients and can be promising sources for food supplementation (Larrea et al 2005;Wandee et al 2014). Several attempts to improve the nutritional profile of extruded starch by using food by-products have been reported (Onwulata et al 2001;Stojceska et al 2008).…”
Section: Introductionmentioning
confidence: 99%